Estratégias de controle coordenado de tensão para sistemas de distribuição com geração eólica - Fiorin, Marcos (2014)
The connection of wind generation to distribution systems can cause power quality problems such as voltage sags and voltage fluctuations. The wind generation can also detrimentally affect the operational and control strategies employed in the distribution systems. On the other hand, the use of suitable control strategies may allow wind generation to mitigate power quality problems related to voltage regulation and to improve the reliability of distribution systems. In this context, this work proposes strategies for coordinated voltage control in distribution systems with wind generation. The proposed control strategies aim at enabling wind generation to contribute to coordinated voltage regulation in the distribution system. The proposed coordinated control with the typical operations of On Load Tap Changer (OLTC) transformers and switched capacitor bank, allows the wind power attenuates voltage variations and voltage fluctuations caused by normal changes in system load and wind speed. The focus of this work is the voltage regulation at the medium voltage bus in the substation, considering the connection of wind generation at this point the system. Control strategies involving the prediction of wind speed are also proposed to improve the performance of the voltage control system, and can be implemented by means of a supplementary control loop add to wind generation unit. The evaluations and validations were based on a distribution system with typical topology and considering actual data for the transmission line and OLTC transformer, as well as real data of wind speed and load curve. The study also evaluates the impact caused by the connection of wind generation, for different penetration levels of generation and different wind power classes, on the voltage magnitude of a distribution system. The obtained results have demonstrated the effectiveness of the proposed strategies in regulating the system voltage and reducing the number of tap changes.